PEMBELAJARAN SENI BUDAYA DI SMA NEGERI 1 NAN SABARIS KABUPATEN PADANG PARIAMAN - Yona, Irma; Wimbrayardi, Wimbrayardi; Hadi, Harisnal (SENDRATASIK UNP, 2019)
Abstract This study was aimed to describe how process of cultural art learning in SMA Negeri 1 Nan Sabaris. In activity, teacher had important role to get the purpose of the study. Teacher had to hold the learning refer to the plan as a reference. Type of this study was qualitative with analitycal descriptive method. The main instrument of this study was the researcher. The assisted tools used in this study were stationery, camera and audio recorder. This study used two data, they were primary and secondary. Moreover, technique of data collection were done by using library research, observation, interview and documenntation. Result of this study showed that the learning of cultural art in SMA Negeri 1 Nan Sabaris had not been accomplished well yet. It was caused in the learning process of cultural art, there was still an irregularity. In cultural art learning in SMA Negeri 1 Nan Sabaris, teacher had to refer to the existing plan, but it was not equipped by adequating facilities. In order to reach the purpose of the study, the school needed to accomplish the facilities which were needed in the learning. Keywords  :  Facilities in cultural art learning